Annual digest of human rights judgements 2004 - "Antony, M.J" (New Delhi, 2007)
The awareness of human rights and the means to enforce them is increasing rapidly among the people, going by the number of petitions filed in the courts and before the human rights commissions. A decade ago, the National Human Rights Commission received only some 500 petitions a year. However, the number of complaints has been increasing at a steady and fast pace over the years. After 2000, it has not gone below 70,000 annually. The complaints were mostly about police excesses, atrocities against the lower castes. communal violence, bonded labour, child labour, dowry deaths, rapes and sexual harassment. The pattern is the same if one examines the petitions filed in the high courts and the Supreme Court. This year's collection of summaries of judgments from the high courts and the Supreme Court affirms this trend. These courts normally deliver more than 300 judgments every year dealing with violations of human rights. Unlike the orders passed by the human rights commissions, the judgments passed by the courts have the force of law and the executive are constitutionally bound to enforce them. The courts also deal with other violations of fundamental rights, like environmental degradation, čivic problems and issues which indirectly affect the basic rights of the people. This volume, the fifth in the series, contains almost all such judgments delivered by the courts.
Keywords: Human rights-Judgements-2004